Present and future of the techniques applied to seasonality studies - Sánchez Flores, Antonio Jesús; Arriaza, Mari Carmen; Sainz de los Terreros, José Yravedra (Journal of Heredity, 2018)
In the mid-twentieth century, the methods of seasonality studies emerged to try to establish the time of year, and the occupation time, in which the archaeological sites were inhabited. However, the limitations of these techniques, based fundamentally on fossil skeletal remains, have hindered the interpretation of these data. This work makes a list of most methods used for seasonal studies so far, in order to facilitate their understanding and application in the future, highlighting the virtues and shortcomings of each. A mediados del siglo XX, los métodos de los estudios de estacionalidad surgieron para intentar establecer el momento del año y el tiempo de ocupación en el que se habitaron los yacimientos arqueológicos. Sin embargo, las limitaciones de estas técnicas, basadas fundamentalmente en restos óseos fósiles, han dificultado la interpretación de estos datos. Este trabajo hace una relación de la mayoría de métodos utilizados para los estudios estacionales hasta la fecha, para facilitar su comprensión y su futura aplicación, destacando las virtudes y los defectos de cada uno.